Analisis Perbandingan Kepentingan PDIP dan Partai Demokrat dalam Menyikapi Presidential Threshold - Sukri, Mhd Alfahjri (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2023)
This study aims to analyze by comparing the political interests of the PDI-P and the Democratic Party in addressing the presidential threshold (PT). The research uses a qualitative method with data sourced from the results of DPR meetings, books, journals and news. The research finding is that the PDI-P and the Democratic Party have a political interest in addressing the presidential threshold. When in power, the Democrat Party initially shared the same view as the PDI-P in supporting PT at least 20-25 percent. However, this attitude changed when the Democratic Party was no longer in power and was unable to nominate a presidential candidate from his party. The Democratic Party after the 2014 election until now has refused PT 20-25 percent and asked for PT 0 percent. Meanwhile, the PDI-P is consistent in supporting the PT 20-25 percent and has always been able to nominate presidential candidates from their own party. PDI-P can nominate president from the party in 2024 because it has passed the minimum PT. The two political parties share an interest, where currently the PDI-P wants to maintain power with a high PT, while the Democrat Party wants to seize power with a low PT so that it can nominate president from its own party.